Ceiling of the Garbhagriha of the Kaner-ki-Putli Temple - Temples of India Project Team (Jio Institute, 2024)
The ceiling of the garbhagriha (sanctum sanctorum) of the Kaner-ki-Putli Temple is square in shape and consists of concentric squares design. It is adorned with a fully bloomed flower in the centre.